Clinical experience of the use of Vasavital® in dry age-related macular degeneration and ischemic optic neuropathy (Ukrainian Journal of Ophthalmology, 2025)
Background: The chronic ischemic process caused by impaired hemodynamics in the eye and brain is a component of the pathogenesis of ischemic optic neuropathy and age-related macular degeneration, and requires prompt and adequate treatment.Purpose: To examine the effect of a one-month course of Vasavital on the function of the visual system and regional hemodynamics in patients with dry age-related macular degeneration and those with ischemic optic neuropathy.Material and Methods: Thirty-two patients with dry age-related macular degeneration (AMD) (mean age, 66 ± 1.5 years) and 22 patients with chronic ischemic optic neuropathy (mean age, 57.0 ± 1.4 years) underwent examination and treatment at the Department of Uveitis and Laboratory for Functional Examination of the Visual System of the Filatov institute. They received a one-month course of Vasavital-only therapy at a dose of one capsule twice a day as an outpatient treatment. Patients reported their complaints and underwent routine eye examination, studies of regional hemodynamics in the eye and brain (by ophthalmic rheography and rheoencephalography with Reocom, the computerized rheography apparatus), and electrophysiological studies of electrically evoked phosphene threshold (EEPT) and critical frequency of phosphene disappearance (CFPD) at two time points: prior to and after a one-month course of Vasavital-only therapy.Results:  A one-month course of Vasavital-only therapy resulted in 24% and 9.6%-25% increases in ocular pulse blood filling in patients with chronic ischemic optic neuropathy and patients with age-related macular degeneration with various baseline levels of visual acuity, respectively. In addition, vascular tone in large-and small-caliber ocular vessels decreased significantly, by 12-17%, in patients with chronic ischemic optic neuropathy, and by 10-20%, in patients with age-related macular degeneration, and vascular tone in large-caliber brain vessels (in the vertebral-basilar system) decreased by 21.6% in patients with ischemic optic neuropathy. A course of Vasavital-only therapy resulted in improved optic nerve function in patients with ischemic optic neuropathy, with a 20.5% improvement in electrically evoked phosphene threshold (EEPT), and 22-63% improvement in critical frequency of phosphene disappearance (CFPD); this indicated an improved function of the peripheral as well as central retina.
Keywords: Vasavital; dry age-related macular degeneration; ischemic optic neuropathy